Chaga mushroom-induced oxalate nephropathy that clinically manifested as nephrotic syndrome: A case report. Issue 10 (11th March 2022) - Kwon, Ohyun; Kim, Yaerim; Paek, Jin Hyuk; Park, Woo Yeong; Han, Seungyeup; Sin, Hyungchan; Jin, Kyubok
Abstract: Rationale: The Chaga mushroom (Hymenochaetaceae, Inonotus obliquus ) is a fungus belonging to the Hymenochaetaceae family. It is parasitic on birch and other tree species. Chaga mushrooms are rich in various vitamins, minerals, and nutrients. Some people consider these mushrooms medicinal as they have been reported to suppress cancer progression through anti-inflammatory and antioxidant effects. However, recent studies have reported that excessive ingestion of Chaga mushrooms can cause acute oxalate nephropathy. Patient concerns: A 69-year-old man who ingested Chaga mushroom powder (10–15 g per day) and vitamin C (500 mg per day) for the past 3 months developed acute kidney injury (AKI) with the clinical manifestations of nephrotic syndrome (NS). Diagnosis: Pathological findings showed focal acute tubular injury and the deposition of calcium oxalate crystals in the tubules. Light microscopy showed interstitial fibrosis and tubular atrophy, and electron microscopy showed the effacement of the foot processes in podocytes. Based on these results, the diagnosis was acute oxalate nephropathy accompanied by minimal change disease (MCD). Interventions: The patient's kidney function did not improve with supportive care, such as hydration and blood pressure control. Thus, we recommended hemodialysis and the administration of a high dose of steroids (intravenous hydrocortisone 500 mg twice a day for 3 days and oral prednisolone at 1 mg/kg). Outcomes: The patient's kidney function recovered just 1 month after the start of treatment, and the MCD was completely remitted. Lessons: In cases of AKI with an unknown cause, it is important to closely observe the patient's medication history, and it is recommended to perform kidney biopsy. Furthermore, this study showed that active dialysis and high-dose steroid treatment can restore kidney function in patients with AKI caused by acute oxalate nephropathy with MCD.